Choice of Approach in Hemiarthroplasty For Intertrochanteric Femur Fractures: Anterolateral or Posterolateral? - Mehmet YETİŞ (Ahi Evran Medical Journal, 2022)
Purpose: Both anterolateral and posterolateral approaches are commonly chosen for hemiarthroplasty in hip fractures. The superiority of these approaches to each other is not well understood. In this study, we aimed to compare the outcomes of posterolateral and anterolateral approaches in hip hemiarthroplasty for intertrochanteric hip fractures. Materials and Methods: 79 patients who had AO type 31-A1, 31-A2 and 31-A3 fractures were divided into two groups: 38 patients in group I underwent anterolateral approach, and 41 patients in group II underwent posterolateral approach. Demographic findings, intraoperative blood loss, operation duration, hospital stay duration, blood transfusion amount, intraoperative and postoperative complications, postoperative mobilization time, preoperative and postoperative serum hemoglobin values, Harris Hip Score, and Likert pain scales were all assessed. Results: There was no significant difference between the groups in terms of age, gender, BMI and AO fracture types, respectively (p=0.356, p=0.981, p=0.343, p=0.631). The mean intraoperative blood loss amount in Group I and II were 413.15 ml (SD±96.34) and 475.60 ml (SD±117.32), respectively (p=0.012). Compatible with this result, the mean postoperative blood transfusion unit in Group I and II were 0.94 units (SD±0.86) and 1.95 unit (SD±1.02), respectively (p<0.001). HHS and Likert scores following both techniques were statistically similar between both groups (p=0.567, p=0.388, respectively). Conclusion: Our results show that hemiarthroplasty with both anterolateral and posterolateral approaches are viable treatments for intertrochanteric femur fractures, yielding similar clinical outcomes and complication rates. Less intraoperative blood loss and postoperative transfusion rates make the anterolateral approach more favorable compared to the posterolateral approach.